2016
DOI: 10.1186/s12906-016-1246-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a standardized mistletoe (Viscum album) preparation with antitumor effects of Trastuzumab in vitro

Abstract: BackgroundBesides conventional anticancer therapy many breast cancer patients use complementary and alternative medicine (CAM) like the medicinal herb mistletoe (Viscum album L.). To gain more knowledge about possible herb-drug interactions between CAM and conventional anticancer medications, in the present in vitro study we investigated the effect of a standardized mistletoe preparation on the action of Trastuzumab, a drug used for the treatment of Her-2 positive breast cancer.MethodsThe Her-2 positive human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
3
27
0
3
Order By: Relevance
“…A meta-analysis of clinical studies that applied VA Iscador preparations concluded that it might have beneficial effects in psychosomatic self-regulation in addition to short-term quality of life-improving effects in cancer patients [34]. The experimentally assessed mode of action of VA comprises induction of apoptosis, inhibition of cell proliferation and angiogenesis of the tumour cells as well as anti-inflammatory and immunomodulatory effects [35][36][37][38]. Thus, the immunomodulatory nature of VA raises the question of whether there are immunologic interactions between VA and inhibitors of the PD-1/PDL-1 or CTLA-4 pathways that might lead to increased toxicity for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of clinical studies that applied VA Iscador preparations concluded that it might have beneficial effects in psychosomatic self-regulation in addition to short-term quality of life-improving effects in cancer patients [34]. The experimentally assessed mode of action of VA comprises induction of apoptosis, inhibition of cell proliferation and angiogenesis of the tumour cells as well as anti-inflammatory and immunomodulatory effects [35][36][37][38]. Thus, the immunomodulatory nature of VA raises the question of whether there are immunologic interactions between VA and inhibitors of the PD-1/PDL-1 or CTLA-4 pathways that might lead to increased toxicity for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Die Ergebnisse einiger weniger hierzu bisher durchgeführter Untersuchungen weisen darauf hin, dass Mistelextrakte kein oder nur ein geringes Risiko für klinische Interaktionen aufweisen. Es handelt sich dabei vorwiegend um präklinische Studien [40][41][42][43][44][45][46]. Eine erste Phase-I-Studie zeigte für ein Mistelpräparat am Patienten, dass die Pharmakokinetik des Zytostatikums Gemcitabin bei paralleler Anwendung von hohen Dosierungen bis zu 250 mg Mistelextrakt nicht beeinflusst wurde [47].…”
Section: Interaktionenunclassified
“…However, in rare cases, a generalised allergic reaction may occur [23,24,47,48]. Unwanted and/or clinically significant interactions with ME and established chemotherapeutic drugs have not been observed [23,40,[49][50][51][52].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%